Patient perceptions of the use of e-cigarettes in smoking treatment programs: a qualitative analysis - Sidney V Rojas; Kelly A. Kyanko; Rachel Wisniewski; Katherine O’Connor; Rina Li; Grace Xiang; Mahathi Vojjala; Olivia Wilker; Scott E. Sherman; Elizabeth R. Stevens (Addiction Science & Clinical Practice)
Abstract Background E-cigarettes may serve as a safer alternative to combustible cigarettes and may be more effective than currently available nicotine replacement therapy (NRT). Little is known about the perceptions of using e-cigarettes as part of a smoking treatment program. The objective of this study was to gain insight into patient-level factors to consider when developing smoking treatment programs that incorporate e-cigarettes. Methods Qualitative analysis of in-depth interviews with 14 participants enrolled in the e-cigarette treatment arm of a tobacco treatment intervention pilot randomized trial comparing the impact of behavioral counseling paired with e-cigarettes or NRT on smoking outcomes. Participants were prompted to share their experiences with the products and the study overall. Transcripts were coded according to the principles of framework analysis for applied research. Codes were organized into themes using the principles of grounded theory. Results Themes suggest that while there is an eagerness to try e-cigarettes as a new tool for smoking cessation, there is apprehension regarding what it means to “quit” if switching to e-cigarettes. Reflecting on the transitional purpose of e-cigarettes and potential health concerns associated with their use, many participants differentiated between the short-term goal to quit combustible cigarettes and the long-term goal to quit e-cigarettes. Conclusions Including e-cigarettes as an option in smoking treatment regimens may be an opportunity to re-engage people who smoke who have tried and failed to quit with other forms of treatment. Participants found it challenging to establish what it means to quit cigarettes with e-cigarettes due to addiction and other health concerns. Clear guidelines are needed for integrating e-cigarettes into smoking cessation programs. Trial Registrations ClinicalTrials.gov Identifier: NCT04465318.